Effects of Copper 0.127 mm Thick Flat Sheet on Uniform and Hot Region Images as A Material Filter for Scatter Correction in Tc-99m SPECT - Sayed, Inayatullah Shah; Harun, Siti Zawani (MEACSE Publications, 2016)
In the SPECT image data, presence of scatter component leads to poor image quality. Consequently, inaccuracy in the diagnosis of disease occurs. This study aims to improve the image quality by reducing some fraction of scattered gamma photons prior to detection using a material filter technique. Data were acquired by scanning a cylindrical source tank with hot/cold regions insert filled with water and uniformly distributed Tc-99m radionuclide. Philip ADAC Forte dual head gamma camera with LEHR collimator was used. Material filter, a flat sheet of Cu 0.127mm thick was attached on the outer surface of the collimator. SPECT data were acquired without and with material filter. Filtered back projection technique was applied. Images were visually examined in order to observe the improvement in image quality of uniform and hot regions as well as the detectability of hot regions. Standard deviation in the count density of uniform region and contrast of hot region images was calculated. Findings of the study reflect an overall enhancement in the image uniformity, hot regions detectability and contrast with material filter. It is concluded that, material filter technique need further investigations for applicability in clinical studies by scanning other phantoms mimicking human organs.